Skin Pigmentation Differences between Mongolian, Korean, and Uzbekistan Ancient Human DNA Samples. (11th August 2020) - Bazarragchaa, Munkhtsetseg; Uuganbayar, Udval; Lee, Kwang-Ho; Kim, Kyung-Yong; Kim, Kijeong
Abstract : Background . This study reports the use of real-time PCR to identify the SNP rs1545397 in the intron region on the OCA2 gene from ancient and degraded DNA isolated from ancient human bones from Mongolia, Korea, and Uzbekistan. This SNP is a marker for skin pigmentation. LightCycler-based probes (HybProbes) were designed. A LightCycler (version 2.0) system was used for the real-time PCR. Results . The results of the real-time PCRs of three different genotypes of SNP rs1545397 were compared with those of the direct sequencing. Melting curve analysis was used for genotype determination. Three genotypes were distinguished: the homozygous T (T/T) SNP type formed a distinct melting peak at 53.3 ± 0.14 ° C, the homozygous A (A/A) SNP type formed a distinct melting peak at 57.8 ± 0.12 ° C, and the heterozygous A/T SNP type formed two distinct melting peaks at 53.3 ± 0.17 ° C and 57.8 ± 0.15 ° C . Mongolian aDNA samples tested in this study carried all three types of the SNP (A/T, A/A, and T/T) with no distinctly predominant type observed. In contrast, Korean aDNA samples carried the Asian genotype (T/T), while the Uzbekistan aDNA samples carried the European genotype (A/A) more often than the Asian genotype (T/T). Conclusions . Human Mongolian aDNA samples had A/T, A/A, and T/T SNP rs1545397 with no distinct predominant genotype. When combined with the archeological and aDNA studies of other coupling morphologies with aDNA, our results infer that Mongolia's prehistoric population had considerable heterogeneity of skin color and morphological traits and that in the Neolithic period, a Eurasian or mixed population inhabited the western part of Mongolia.